Validating Educational Game Development to Foster Learning Motivation in Elementary School Students - Shofie Putriningtyas; Unik Ambarwati (Universitas Pendidikan Ganesha, 2024)
One of the causes of low student learning motivation is the lack of engaging and need-based instructional media developed by teachers for specific subjects. Educational games can foster intrinsic motivation by stimulating students' curiosity, thereby supporting the teaching and learning process in formal educational environments. This study aims to analyze the validity of an educational game developed to enhance students' learning motivation through a validity test. The development process employed the Research and Development (R&D) model recommended by Borg and Gall. Data collection instruments included validation sheets from media, material, and language experts, a media usage guidebook, observation guidelines for media implementation in learning, interview guidelines for teachers and students, and a student motivation instrument. The data analysis technique used was descriptive quantitative analysis. The validity test results indicated that the media's validity level was categorized as good. The product quality category from the instrument experts showed a score of 0.785. Since the Cronbach's Alpha value was 0.785, which is greater than 0.60, it can be concluded that the reliability test was deemed reliable. Therefore, the educational game developed is considered feasible and effective for improving students' learning motivation in elementary schools.